The Effect of Accountability and Transparency on the Effectiveness of Fund management BOP With Parental Participation As Moderating Variables - Nisa, khairi; Putri, Anne (Adpebi International Journal of Multidisciplinary Sciences, 2022)
This study aims to determine the effect of accountability, transparency on the effectiveness of the management of operational assistance funds for early childhood management (BOP Paud) in Arrudhah Taluak IV Tribe Islamic Kindergarten with parental participation as a moderating variable. The sample of this research was obtained as many as 110 respondents. PLS SEM analysis method, this research instrument uses google form. The type of research used in this research is quantitative research. Based on the results of the research that has been done, it was found that accountability has a significant effect on the effectiveness of BOP fund management, Transparency has a significant effect on the effectiveness of BOP fund management, Parental participation has a significant effect on the effectiveness of BOP fund management. Parental participation as moderator has a negative and insignificant effect on accountability, transparency and effectiveness of BOP fund management in Islamic Kindergarten Arraudhah Taluak IV Suku